Aquecimento magnético de uma gota de ferrofluido combustível: modelagem de micro-explosão e acúmulo de nanopartículas na superfície - Zorzo, Régis (2019)
The present work presents a theoretical model that describes the heating and vaporization of a combustible ferrofluid droplet due to the action of an external and alternating magnetic field (magnetic heating) together with the heat flux provided by the gaseous environment. Magnetic heating is the result of the interaction between the magnetic field and the ferrofluid magnetic nanoparticles. The combined effect of heat transfer from ambient to droplet with magnetic heating, together with heat loss from the vaporizing surface, results in a temperature profile with the boiling point within the droplet. This is a characteristic bubble-forming effect that may cause the droplet micro-explosion. In the present work, it is considered that the droplet rupture (break) occurs at the moment when the boiling condition is reached inside, generating a secondary droplet. After breaking, the primary droplet continues to be heated and vaporized, generating new secondary droplets whenever the boiling temperature is reached inside. The results are obtained considering two cases, in the first case all surface nanoparticles vaporize, maintaining their constant concentration inside the droplet. In the second case, there is an accumulation of nanoparticles on the droplet surface, causing a variation in the concentration of nanoparticles. Results are presented as a function of some parameters such as magnetic power, magnetic field frequency, ambient temperature and initial droplet temperature. It was possible to notice that the formation frequency and the number of secondary drops increase with the magnetic power. The droplet-breaking process has a great influence on the effective vaporization rate and the decrease of the initial droplet radius. Considering the accumulation of nanoparticles on the surface, it was found that for cases where the fraction of nanoparticles that accumulates on the surface is high, the vaporization rate may decrease, depending on the heat generated by the magnetic heating.